Preschool children's prosocial behavior: A correlational study of mother's roles - Ulwan Syafrudin; Sri Wahyuni; Rizky Drupadi (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to determine the relationship between the mother's role and the prosocial behaviour skills of children aged 5-6. The type of research used is non-experimental with a correlational approach. The sample consisted of 40 mothers with children aged 5-6 years and 40 children aged 5-6 years at TK IT Insan Taqwa, Lampung, Indonesia. The data collection technique is a questionnaire. The data analysis technique uses the Spearman Rank correlation test. The study results indicate a strong relationship between the role of the mother and the ability to prosocial behaviour, which consists of 6 roles; educators, encouragement, role models, friends, supervisors, and counsellors. The correlation coefficient value for the mother's role is 0.69, with a close relationship to the prosocial behaviour of sharing, collaborating, being honest, donating, helping, and considering the welfare of other individuals. The relationship between parties in the child's immediate environment and social behaviour can be used for further research.